Aplikasi Tiktok Terhadap Perilaku dan Karakter Siswa Sekolah Dasar - Harina Sangadji (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
Tiktok has recently become a trend among young people, especially for elementary school children. This type of research is qualitative research that we conducted in class V of SDN 14 Ternate City. The data collection technique in this research is using descriptive methods. Documentation data is the student's character, namely attitudes and behavior that are obedient in carrying out the teachings of the religion they adhere to as well as actions that show orderly behavior and compliance with various rules and regulations. Data analysis uses statistical analysis, namely interpretation and conclusions made based on statistical analysis to find out how much influence the use of social media has on students' character. The research results show that there is a significant influence of the use of TikTok social media on students' character. From the results of preliminary research conducted by analysts, results were obtained which stated that the use of the online media TikTok can influence the student's character. So this TikTok application-based media is an external factor that influences student character. Many of them use online media too often, which makes them lazy to learn. In addition, it is very disappointing for students' actual learning results the next day. language development, facilitate better communication, and understanding of their social environment.